2014
DOI: 10.1002/2014gl060375
|View full text |Cite
|
Sign up to set email alerts
|

Location and analysis of acoustic infrasound pulses in lightning

Abstract: Acoustic, VHF, and electrostatic measurements throw new light onto the origin and production mechanism of the thunder infrasound signature (<10 Hz) from lightning. This signature, composed of an initial compression followed by a rarefaction pulse, has been the subject of several unconfirmed theories and models. The observations of two intracloud flashes which each produced multiple infrasound pulses were analyzed for this work. Once the variation of the speed of sound with temperature is taken into account, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 23 publications
3
22
1
1
Order By: Relevance
“…The detection of lightning infrasound from strokes at more than several tens of kilometers from the ULDB does not support the theory that acoustic wavefields generated by lightning infrasound are strictly oriented vertically. Instead, the waveforms here share amplitude, frequency, and range detection characteristics with previously recorded lightning infrasound signals which were attributed to charge deposition in the lightning channels (e.g., Arechiga et al, ; Farges & Blanc, ). The electrostatic forces caused by the charge deposition may cause the air in the streamer zone to expand, producing an acoustic compression wave whose period corresponds to the size of the streamer zone (Arechiga et al, ).This is in addition to the rapid air expansion generated by extreme heating of the lightning channel that produces audible and infrasonic acoustic waves (Few et al, ).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…The detection of lightning infrasound from strokes at more than several tens of kilometers from the ULDB does not support the theory that acoustic wavefields generated by lightning infrasound are strictly oriented vertically. Instead, the waveforms here share amplitude, frequency, and range detection characteristics with previously recorded lightning infrasound signals which were attributed to charge deposition in the lightning channels (e.g., Arechiga et al, ; Farges & Blanc, ). The electrostatic forces caused by the charge deposition may cause the air in the streamer zone to expand, producing an acoustic compression wave whose period corresponds to the size of the streamer zone (Arechiga et al, ).This is in addition to the rapid air expansion generated by extreme heating of the lightning channel that produces audible and infrasonic acoustic waves (Few et al, ).…”
Section: Discussionsupporting
confidence: 51%
“…Validation of the production mechanism and acoustic wavefield has been confounded by the difficulty in locating the charge layers in the storm cloud, as well as characterizing the structure of the parent lightning flash. Advancements in location algorithms and instruments deployments such as the Lightning Mapping Array have produced observations that refute the previously proposed production mechanisms (Arechiga et al, ). Instead, the observations suggest that the infrasonic signals from lightning flashes may be produced by electrostatic interaction of charge deposited in the streamer zone of a lightning channel; that is, acoustic compression waves may be generated by electrostatic forces causing air within the streamer zone to expand (Arechiga et al, ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Infrasound observations provide some lightning characteristics (Farges 2009). Recent studies have shown that the 3D geometry of intra-cloud discharges can be reconstructed using thunder measurements by a small-aperture (25-50 m) array of microphones (Arechiga et al 2014;Gallin 2014). An example of infrasound inversion, providing the origin of the infrasound sources inside the lightning structure, is shown in Fig.…”
Section: Infrasound Used For Lightning Source Descriptionmentioning
confidence: 99%